Upaya Preventif Orang Tua Dalam Mengantisipasi Kekerasan Seksual Terhadap Anak (Studi Kasus di Desa Salem Kecamatan Pondoksalam Kabupaten Purwakarta) - Nurzakiyah, Kiki Rizki; Siswanto; Gussevi, Sofia (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This research is motivated by the many cases of sexual violence against children as victims, one of which occurred at the Miftahul Huda Assembly, Salem Village, Pondoksalam District, Purwakarta Regency. Acts of sexual violence against children can cause physical, psychological, social, prolonged trauma, and potentially make them perpetrators of sexual violence in the future. Therefore, the role of parents is very important through the rights and obligations of parents to children in preventing sexual violence against children. The purpose of this study is to describe the efforts made by parents in preventing sexual violence against children, parents' views on sexual violence that occurs in recitation, and the supporting and inhibiting factors experienced by parents in preventing sexual violence. The theory used in this study is the theory of social control developed by Travis Hirschi about things that can restrain a person from committing social deviations or violations. The research approach used is a descriptive type qualitative approach. Research informants were selected using purposive sampling technique, namely, parents (father or mother) who have children aged 12-15 years and have never experienced sexual violence. The data collection method used was obtained through observation, in-depth interviews and documentation. The results of this study indicate that parents view sexual abuse in recitation as something that is not right and violates the rules. Parents' efforts in preventing sexual violence against children by instilling religious teachings as a foundation, providing a good environment, teaching responsibility and discipline, providing boundaries in relationships, and building good communication. The obstacles or difficulties of parents in providing supervision and in terms of explaining body parts to children are still taboo feelings and emotions, lack of knowledge and skills as well as limited time and distance. While supporting factors or those that help parents are the presence of close family, media and technology, and the existence of educational institutions.